Contribution of the Nursing Medical Committee to Enhancing Inpatient Service Quality at Labuang Baji Hospital, Makassar - Andi Khairul Musyawir; Momen Amalia; Fitri Asfa Asmot (International Journal of Public Health, 2025)
The medical committee is a non-structural body whose members are selected from among the heads of functional medical staff (SMF) or those representing SMF in the hospital. Objective : This study aims to evaluate the role of the nursing medical committee and its influence on the quality of inpatient services at Labuang Baji Hospital Makassar. Method : Analytic descriptive method with the design used crosssectional design Result : Logistic regression analysis showed a significant influence between the role of the medical committee and the quality of inpatient services with a value of p=0.002. Further quality of inpatient services with a value of p=0.002. Further logistic regression analysis showed that the role of the medical committee had a very large influence on service quality, with an Exp(B) value of 44,000. This indicates that each increase in the role of the medical committee can increase the likelihood of good service quality by 44 times. Overall, the results of this study indicate that the role of the nursing medical committee is very influential in improving the quality of inpatient services at Labuang Baji Hospital Makassar. This finding is expected to be the basis for developing strategies to improve service quality in the hospital. Suggestion : Ensure that the roles and responsibilities of the medical committee and nurses are clear and mutually supportiveThe medical committee should have a deep understanding of the care process, while nurses need to know how the role of the medical committee can influence and support their practice.